America's Maritime Heritage - Engle Eloise; Lott Arnold S. (Naval Institute Press, 1975)
Foreword, Preface, Acknowledgements, The Days of Growth, Colonial America, Colonial Seaports, Ships Overseas, The Years of Achievements, The Paths of the Sea, Piracy and Slavery, The Civil War, A Century of Progress, Sociology and Education, Technology, Global War, Our Cultural Heritage, Sea Power and National Survival, Bibliography, Index.
Foreword, Preface, Acknowledgements, The Days of Growth, Colonial America, Colonial Seaports, Ships Overseas, The Years of Achievements, The Paths of the Sea, Piracy and Slavery, The Civil War, A Century of Progress, Sociology and Education, Technology, Global War, Our Cultural Heritage, Sea Power and National Survival, Bibliography, Index.